IDENTIFICATION OF INDICATIONS TO VERTEBRAL CANAL DECOMPRESSION IN PATIENTS WITH KYPHOTIC DEFORMITIES OF THORACIC AND LUMBAR SPINE - O. B. Chelpachenko; K. V. Zherdev; A. A. Ovechkina (Педиатрическая фармакология, 2014)
Relevance. Vertebral canal revision and decompression in patients with kyphotic deformities of thoracic and lumbar spine is performed not only in the setting of severe neurological symptoms, but also in the presence of risk of neurological deficiency associated with vertebral canal stenosis at the peak of vertebral deformity. There is no common method of measuring vertebral canal loss at the moment; this significantly complicates identification of indications to vertebral canal revision and decompression. The study was aimed at identifying indications to vertebral canal revision and decompression at operative treatment of long kyphotic deformities of thoracic and lumbar spine based on the method of measuring the relative vertebral canal’s stenotic area at the peak of deformity. Patients and methods. Operative treatment was performed in 108 study subjects with kyphotic deformities of thoracic and lumbar spine. The authors developed an original method of measuring the relative vertebral canal’s stenotic area in order to identify indications to vertebral canal revision and decompression. Measurement results were compared with vertebral canal stenosis thresholds for specific localizations. Results. Vertebral canal stenosis was revealed in 43 out of 108 patients (39.81%). Conclusion. The authors developed the first highly accurate method of measuring the relative vertebral canal’s stenotic area, which takes into consideration not only the anteroposterior dimension of the vertebral canal, but also narrowing thereof along its cross-sectional area. Exceedance of the vertebral canal loss threshold is an absolute indication to vertebral canal revision and decompression.